Late immune-related adverse events in long-term responders to PD-1/PD-L1 checkpoint inhibitors: A multicentre study. (July 2020) - Nigro, Olga; Pinotti, Graziella; De Galitiis, Federica; Di Pietro, Francesca Romana; Giusti, Raffaele; Filetti, Marco; Bersanelli, Melissa; Lazzarin, Alessandro; Bordi, Paola; Catino, Annamaria; Pizzutilo, Pamela; Galetta, Domenico; et al.
Abstract: Background: Data on spectrum and grade of immune-related adverse events (irAEs) in long-term responders to immune checkpoint inhibitors (ICIs) are lacking. Methods: We performed a retrospective multicenter study to characterized irAEs occurring after a 12-months minimum treatment period with PD-(L)1 ICIs in patients with advanced cancer. IrAEs were categorized into 'early' (≤12 months) and 'late' (>12 months). Results: From September 2013 to October 2019, 436 consecutive patients were evaluated. Two hundred twenty-three experienced any grade early-irAEs (51.1%), whereas 132 experienced any grade late-irAEs (30.3%) (p < 0.0001). Among the latter, 29 (22%) experienced a recurrence of an early-irAEs, whereas 103 (78%) experienced de novo late-irAEs involving different system/organ. Among patients with late-irAEs, 21 experienced GIII/GIV irAEs (4.8%). Median time to onset of early-irAEs was 3.4 months (95% confidence interval [CI]: 2.8–4.2), whereas the median time to onset of late-irAEs was 16.6 months (95% CI: 15.8–17.6). Cumulative time-adjusted risk of disease progression according to both the early-irAEs (hazard ratio [HR] = 0.63 [95% CI: 0.30–1.29], p = 0.204) and late-irAEs occurrence revealed no statistically significant differences (HR = 0.75 [95% CI: 0.37–1.56], p = 0.452). In addition, the time-adjusted cumulative risk of death in accordance with both early-irAEs (HR = 0.79 [95% CI: 0.34–1.86], p = 0.598) and late-irAEs (HR = 0.92 [95% CI: 0.49–1.74], p = 0.811) did not show statistically significant differences. Conclusion: Although less frequent than early-irAEs, late-irAEs are quite common in long responders to PD-(L)1 ICIs and are different in terms of spectrum and grade. Time-adjusted analysis revealed that the cumulative risk of disease progression and death were not significantly reduced in patients who experienced late-irAEs. Highlights: Clinical trial adverse events methods do not consider the duration of treatment. Study confirms spectrum of immune-related adverse events (irAEs) described in clinical trials and real-life studies. Among late-irAEs, cutaneous, endocrine and gastrointestinal were the most common. Early-irAEs were not related with progression-free survival and overall survival, late-irAEs were associated with them. Time-adjusted progression risk was not reduced in accordance with early- and late-irAEs.